2012
DOI: 10.7771/1541-5015.1355
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based and Project-based Learning in Engineering and Medicine: Determinants of Students’ Engagement and Persistance

Abstract: This paper presents results of a study conducted with undergraduate students involved in either problem-or project-based curricula (Medicine and Engineering, respectively) at the Université de Sherbrooke, Canada. The objective of the present research was to measure the impact of these innovative curricula on students' engagement and persistence in higher education. Our research question was: What determinants better predict students' engagement and persistence in innovative curricula such as PBL? Nine variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 36 publications
(37 reference statements)
2
66
1
9
Order By: Relevance
“…Although prior studies of PBL have explored specific motivation constructs such as self-efficacy (Bédard, Lison, Dalle, Côté, & Boutin, 2012;Dunlap, 2006) and specific components of course design such as group processes and student resources (Henry, Tawfik, Jonassen, Winholtz, & Khanna, 2012), few if any studies have provided a holistic exploration of established motivation constructs and concrete elements of PBL pedagogies such as the one described in this study. It is noteworthy that while the descriptions of PBL such as those provided by Hmelo-Silver (2004), de Graaf and, and Savery (2006) suggest that PBL can foster students' positive perceptions of the MUSIC components, poorly implemented PBL can risk fostering negative perceptions.…”
Section: The Music Model and Pblmentioning
confidence: 99%
See 2 more Smart Citations
“…Although prior studies of PBL have explored specific motivation constructs such as self-efficacy (Bédard, Lison, Dalle, Côté, & Boutin, 2012;Dunlap, 2006) and specific components of course design such as group processes and student resources (Henry, Tawfik, Jonassen, Winholtz, & Khanna, 2012), few if any studies have provided a holistic exploration of established motivation constructs and concrete elements of PBL pedagogies such as the one described in this study. It is noteworthy that while the descriptions of PBL such as those provided by Hmelo-Silver (2004), de Graaf and, and Savery (2006) suggest that PBL can foster students' positive perceptions of the MUSIC components, poorly implemented PBL can risk fostering negative perceptions.…”
Section: The Music Model and Pblmentioning
confidence: 99%
“…These results extend findings from other studies that examine motivation-related constructs in PBL environments. Though work on motivation theory and PBL is still young, some work has been conducted to explore constructs such as self-efficacy (Dunlap, 2006) and engagement (Bédard et al, 2012). For example, whereas Bédard et al (2012) found no direct predictive link between self-efficacy and engagement in the PBL environment, their work did indicate that supports (e.g., opportunities for personal growth) and reflexive thinking, which align with the MUSIC model constructs, do predict curricular engagement.…”
Section: Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative learning and facilitator support can contribute to students' success beliefs by allowing them to engage in mastery experiences. The reflective components of PBL can also contribute to higher levels of individual interest in helping students explicitly articulate their growing comprehension of the real work (Hasna, 2008;Bédard et al, 2012).…”
Section: Problem-based Learningmentioning
confidence: 99%
“…Despite an increasing of publications, few studies have provided systematic evidence of PBL (Galand et al, 2012;Jones et al, 2013). Moreover, the adoption of PBL in engineering education is usually adapted to existing program structures and outcomes, which may change the PBL approach from its roots in medical schools, and suggests a potential lack of PBL research in engineering education (Distlehorst et al, 2005;Bédard et al, 2012). …”
Section: Introductionmentioning
confidence: 99%